Evolution of GABAergic circuitry in the mammalian medial geniculate body. - Winer, J A (1996)
Many features in the mammalian sensory thalamus, such as the types of neurons, their connections, or their neurotransmitters, are conserved in evolution. We found a wide range in the proportion of gamma-aminobutyric acidergic (GABAergic) neurons in the medial geniculate body, from <1% (bat and rat) to 25% or more (cat and monkey). In the bat, some medial geniculate body subdivisions have no GABAergic cells. Species-specific variation also occurs in the somesthetic ventrobasal complex. In contrast, the lateral geniculate body of the visual system has about the same proportion of GABAergic cells in many species. In the central auditory pathway, only the medial geniculate body shows this arrangement; the relative number of GABAergic cells in the inferior colliculus and auditory cortex is similar in each species. The range in the proportion of GABAergic neurons suggests that there are comparative differences in the neural circuitry for thalamic inhibition. We conclude that the number of GABAergic neurons in thalamic sensory nuclei may have evolved independently or divergently in phylogeny. Perhaps these adaptations reflect neurobehavioral requirements for more complex, less stereotyped processing, as in speech-like communication.